2015
DOI: 10.1515/hf-2015-0141
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of brown rot decay resistance of thermally modified wood: resistance to Fenton’s reagent

Abstract: Abstract:The resistance of heat treated (HT) wood to brown rot fungi has been investigated, while the role of the Fenton reaction (FR) in the initial phase of degradation was in focus. Micro-veneers made of Scots pine, were HT with various intensities and their mass losses (ML HT ) were determined before soaking with a solution of Fenton's reagent containing Fe ions and hydrogen peroxide. The mass loss of the veneers treated that way (ML FT ), their tensile strength loss (TSL FT ) and the H 2 O 2 decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…This is in accordance with Hosseinpourpia and Mai, who showed that diffusion of iron was inhibited in acetylated wood with a high WPG [102]. A similar experiment was performed on thermally modified wood, which showed a significant reduction in iron diffusion in this material but no threshold [91].…”
Section: Diffusion In Modified Woodsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in accordance with Hosseinpourpia and Mai, who showed that diffusion of iron was inhibited in acetylated wood with a high WPG [102]. A similar experiment was performed on thermally modified wood, which showed a significant reduction in iron diffusion in this material but no threshold [91].…”
Section: Diffusion In Modified Woodsupporting
confidence: 89%
“…In vitro studies mimicking both the oxidative and the enzymatic brown rot degradation processes have shown that even though the wood modification provides some protection against degradation by Fenton derived OH radicals, the radicals were able to depolymerise wood polysaccharides in acetylated, DMDHEU-treated and thermally modified wood [89][90][91][92]. Furthermore, fungal cellulases were able to degrade the wood polysaccharides in acetylated and DMDHEU-treated materials but at a slower rate than in untreated wood [85,89].…”
Section: Fungal Response To Wood Modification and Inhibition Of Decaymentioning
confidence: 99%
“…Hosseinpourpia & Mai (2016a, 2016c have conducted a series of experiments where modified wood veneers are exposed sequentially to solutions of iron ions and hydrogen peroxide, mimicking the oxidative Fenton chemistry of brown-rot fungi. Their results show that for acetylated and phenol-formaldehyde modified wood, hydrogen peroxide is not consumed in a solution with iron ions and modified wood after 48 hours of exposure given that the modification intensity (WPG) is high enough (Hosseinpourpia & Mai 2016a. Moreover, controls of modified wood of adequately high WPG exposed only to the iron ion solution did not take up iron during the 48 hour experiment.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…The process is traditionally characterised by low heating rates (<50 °C.min -1 ) and by a relatively long reactor residence time (typically higher than 30 minutes) [3]. The resulting product is intermediate between wood and charcoal and exhibits several advantages when compared to the original material such as an increased energy density [4], a decreased hygroscopicity, a dimensional stabilization [4], an increased resistance to biological decay [5], a loss of mechanical resilience [6], etc. Several studies have shown the efficiency of heat treatment on easing biomass grinding.…”
Section: Introductionmentioning
confidence: 99%